ĐÁNH GIÁ NGUY CƠ SÓNG THẦN Ở CÁC VÙNG VEN BIỂN VIỆT NAM - Thành, Trần Thị Mỹ; Xuyên, Nguyễn Đình; Xuyên, Nguyễn Đình; Dương, Nguyễn Văn; Dương, Nguyễn Văn; Minh, Nguyễn Lê; Minh, Nguyễn Lê (Vietnam Journal of Earth Sciences, 2011)
Evaluation of the Tsunami hazards along the coast of Vietnam In this paper, based on current seismic and geological information and data, we have reviewed and rechecked the accuracy of the hidden Tsunami sources in the South China Seas that have been used in previous studies. We built various scenarios associated with each source and used MOST - a program commonly used by USGS and the rest of the world to study tsunamis - to evaluate the tsunami hazards along the coast of Vietnam and offshore islands. The tsunami wave propagation time, and wave heights at shore for each scenario have been calculated. The findings presented in this paper will provide a more accurate and detailed evaluation of the tsunami hazards along the coast of Vietnam and offshore islands.